1989
DOI: 10.1159/000238681
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Experimental Zygomycosis in Guinea Pigs with Azoles and with Amphotericin B

Abstract: Nonpredisposed Albino guinea pigs were infected intravenously with Rhizopus microsporus var. rhizopodiformis or with Rhizopus oryzae. Both strains were highly pathogenic. They killed all control animals between days 4 and 7 and between days 5 and 9 after infection, respectively. All animals presented invasion of almost all internal organs and skin eruptions developing into ulcers. Oral treatment with ketocon-azole, itraconazole, fluconazole or saperconazole was inefficacious. Parenteral treatment with amphoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…Nevertheless, cultures showed that spores remained viable in the tissues. These results are in accordance with previous studies that showed that amphotericin B prolonged survival in infected animals but did not clear the fungus from the organs (16,28). The two azoles tested in this study were not effective in vivo against R. oryzae despite their relatively low MICs, and similar results have been reported for itraconazole (16,28).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, cultures showed that spores remained viable in the tissues. These results are in accordance with previous studies that showed that amphotericin B prolonged survival in infected animals but did not clear the fungus from the organs (16,28). The two azoles tested in this study were not effective in vivo against R. oryzae despite their relatively low MICs, and similar results have been reported for itraconazole (16,28).…”
supporting
confidence: 93%
“…The other antifungal agents, including the azoles, are considered ineffective (11,20). Nevertheless, in vitro susceptibility data have been limited to a small number of isolates, and there have been few in vivo studies in animal models (3,6,8,14,16,21,24,27,28). Moreover, zygomycetes constitute a heterogeneous group for antifungal susceptibility (2).…”
mentioning
confidence: 99%
“…Consistent with these results, previous studies using a similar model of disseminated zygomycosis in nonneutropenic mice have demonstrated that amphotericin B prolonged survival in infected animals but did not clear the fungus from any of the organs tested (19). Using nonimmunocompromised guinea pigs, similar results were obtained in animals infected with R. oryzae (19,33). Only one study showed amphotericin B clearing the fungal infection from most of the organs in guinea pigs infected with R. microsporus (33).…”
mentioning
confidence: 61%
“…Amphotericin B is the treatment of choice for these infections, and the other antifungal drugs, including the azoles, are considered ineffective against zygomycetes (13,28). Nevertheless, in vitro susceptibility data for zygomycetes obtained with standardized techniques have been limited to a small number of isolates and there have been few studies that examine the in vivo efficacy of antifungals in experimentally infected animals (7,8,19,30,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal studies revealed that itraconazole was completely ineffective against Rhizopus and Mucor spp. even though the isolates were susceptible in vitro (28,29,159). In contrast, itraconazole did have activity in vivo against a hypersusceptible strain of Absidia (MIC, 0.03 g/ml).…”
Section: Antifungal Therapymentioning
confidence: 91%